Salmonella Typhimurium and Multidirectional Communication in the Gut - Gart, Elena V.; Suchodolski, Jan S.; Welsh, Thomas H.; Alaniz, Robert C.; Randel, Ronald D.; Lawhon, Sara D. (Frontiers in Microbiology, 2016)
The mammalian digestive tract is home to trillions of microbes, including bacteria, archaea, protozoa, fungi and viruses. In monogastric mammals the stomach and small intestine harbor diverse bacterial populations but are typically less populated than the colon. The gut bacterial community (microbiota hereafter) varies widely among different host species and individuals within a species. It is influenced by season of the year, age of the host, stress and disease. Ideally, the host and microbiota benefit each other. The host provides nutrients to the microbiota and the microbiota assists the host with digestion and nutrient metabolism. The resident microbiota competes with pathogens for space and nutrients and, through this competition, protects the host in a phenomenon called colonization resistance. The microbiota participates in development of the host immune system, particularly regulation of autoimmunity and mucosal immune response. The microbiota also shapes gut-brain communication and host responses to stress; and, indeed, the microbiota is a newly recognized endocrine organ within mammalian hosts. Salmonella enterica serovar Typhimurium (S. Typhimurium hereafter) is a food-borne pathogen which adapts to and alters the gastrointestinal (GI) environment. In the GI tract, S. Typhimurium competes with the microbiota for nutrients and overcomes colonization resistance to establish infection. To do this, S. Typhimurium uses multiple defense mechanisms to resist environmental stressors, like the acidic pH of the stomach, and virulence mechanisms which allow it to invade the intestinal epithelium and disseminate throughout the host. To coordinate gene expression and disrupt signaling within the microbiota and between host and microbiota, S. Typhimurium employs its own chemical signaling and may regulate host hormone metabolism. This review will discuss the multidirectional interaction between S. Typhimurium, host and microbiota as well as mechanisms that allow S. Typhimurium to succeed in the gut.